THE INFLUENCE OF THE USE OF WEBLOGS AND LEARNING JOURNALS ON THE LEARNING OUTCOMES OF STUDENTS’ AQIDAH AKHLAK AT MADRASAH TSANAWIYAH NEGERI FAKFAK - Ayub, Satry; Yaumi, Muhammad; Usman, Usman (Program Pascasarjana, UIN Alauddin Makassar, 2022)
The aims of this study are: 1) Examining the influence of weblogs in the teaching and learning process in aqidah akhlak learning at Madrasah Tsanawiyah Negeri Fakfak. 2) Revealing the influence of using learning journals in the teaching and learning in aqidah akhlak learning at Madrasah Tsanawiyah Negeri Fakfak. 3) Testing the difference in the influence of weblogs and learning journals on learning outcomes in learning aqidah akhlak at Madrasah Tsanawiyah Negeri Fakfak. This type of research was quantitative with a Quasi-Experimental Design research design. The research approach used numbers and managing statistics. The population in this study were all students at Madrasah Tsanawiyah Negeri Fakfak, with the students of class VIII/B and VIII/C as the sample. Furthermore, the data collection methods were questionnaires and tests, data analysis techniques using descriptive statistical techniques and inferential analysis. The results showed that based on the results of the pre-test and post-test conducted by the researchers, there was an influence of the use of weblogs and learning journals on the learning outcomes of aqidah akhlak in Madrasah Tsanawiyah Negeri Fakfak. There was a significant difference in the post-test results between the weblogs class and the class with the application of learning journals.